STUDI KASUS PADA LANSIA PENDERITA HIPERTENSI DENGAN MASALAH KEPERAWATAN ANSIETAS DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM - Putri, Yulia Devi; Badri, Isna Aglusi; Gustina, Nurma Zela (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Hypertension is the number 1 disease that often occurs in the elderly in Indonesia. Riskesdas data for 2018 showed that hypertension was 34.1% (Riskesdas, 2018). Sample Registration Survey data shows that hypertension is the third largest cause of death in Indonesia with a presentation of 6.7% after stroke and heart disease. The aim of this case study is to provide nursing care for hypertension sufferers with relaxation and knowledge to reduce anxiety in the Sei Langkai Community Health Center Working Area, Batam City. This research uses a descriptive method based on the stages of nursing care including assessment, diagnosis, intervention, implementation and nursing evaluation. The results obtained after nursing care were anxiety nursing problems, the client said he understood his health condition and that made him calmer and less anxious and there was a decrease in the GAI score: 9, blood pressure: 160/100 mmHg, a GAI score: 5, blood pressure: 140/80 mmHg, after being given relaxation and knowledge. It is hoped that it can be used as learning material and reference material in providing nursing care to anxiety patients.